Suppression of B lymphocyte differentiation by newborn T lymphocytes with an Fc receptor for IgM - Hayward, A. R. (1978)
The IgM (Fc)-binding subpopulation of human newborn T lymphocytes (T(M)) suppressed the pokeweed mitogen induced differentiation of adult B lymphocytes. Positively isolated IgG (Fc)-binding T lymphocytes (T(G)) also suppressed, but lymphocyte preparations negatively enriched for T(G) by the depletion of T(M) cells were not suppressive. The Fc receptor specificity of the human newborn suppressor appears to resemble that of the human Con A suppressor.